Pregnancy by oocytes in vitro maturation in amenorrhoeic patient with history of anorexia nervosa - Vargas Tominaga, Luis (2014)
Oocytes in vitro maturation (IVM) usually used in patients with polycystic ovaries and polycystic ovary syndrome has been applied for the treatment of infertility in a woman with secondary amenorrea and history of anorexia nervosa. After repeated unsuccessful attempts of ovarian stimulation for conventional techniques of assisted reproduction, IVM treatment was begun by stimulating the ovaries with rFSH during the second, third and fourth day of the cycle and aspiring antral follicles on the eighth day. There were four cumulus-oocyte complexes that were cultivated in the maturation media for 36 hours in presence of FSH and hCG. Mature metaphase II oocytes were fertilized by intracytoplamatic sperm injection (ICSI) and embryos were frozen by vitrification on the second day. A month later, the endometrium was prepared with estradiol valerate. Thawed embryos were cultivated for 24 additional hours and three embryos were transferred. The patient achieved an evolutionary single gestation with active embryo.